A case of leucism in the Rock catfish, Rhamdia laticauda (Siluriformes, Heptapteridae) in the Northeast of Oaxaca, Mexico - Julián-Caballero, César Camilo (2023)
Here, we report the first observation of a leucistic specimen in the Rock catfish, Rhamdia laticauda in the Northeast of Oaxaca, Mexico. We caught the specimen by electric fishing and then photographed during an ichthyological survey carried out in the Tehuacán-Cuicatlán Biosphere Reserve in the Xiquila River of the upper Papaloapan River basin. The live catfish showed a lack of pigment in the skin, white spots, and normal eye color. This information contributes to the knowledge about intraspecific variability and natural history of R. laticauda. We discuss the potential causes of this color anomaly.